Evaluating factors in urban dengue prevention and control during Indonesia's COVID-19 - Boerman, Baequni; Nasir, Narila Mutia; Karyadi, Karyadi (International Journal of Public Health Science (IJPHS), 2025)
Amidst the COVID-19 pandemic, dengue hemorrhagic fever (DHF) persisted as a critical public health challenge in South Tangerang. This study employed a cross-sectional design and snowball sampling technique to evaluate the engagement of urban communities in dengue prevention, involving 234 participants. Findings indicate that while practices such as container emptying (76.5%) and water storage sealing (57.7%) were prevalent, activities like mosquito larvae inspection (36.3%) and breeding item disposal (34.6%) were less common. Alarmingly, personal protective measures, including mosquito net usage (11.1%) and repellent application (16.7%), were significantly lacking. Statistical analyses revealed notable correlations (p-value<0.05) between dengue prevention behaviors and factors, including beliefs, attitudes towards prevention, support from family and healthcare professionals, and knowledge about dengue prevention. The study highlights a critical disparity in dengue prevention efforts, showing a community bias towards environmental management over personal protection strategies. It calls for increased participation from families and healthcare professionals in dengue prevention initiatives and stresses the need for governmental interventions to improve training for healthcare workers. Ultimately, the study advocates for a comprehensive approach that merges environmental management with personal protective measures, urging governments to adopt integrated strategies for more effective dengue prevention.